ANALISIS PENERAPAN KAIDAH YUKHTARU AHWANU SYARRAINI DALAM CERAI GUGAT KARENA SUAMI HILANG - Ramzy Kidung Arasy; Isnain La Harisi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This study examines the application of the rule of Yukhtaru Ahwanu Syarraini in cases of divorce due to a missing husband, focusing on Religious Court Decision Number 1868/Pdt. G/2024/PA.Grt. The main problem in this research is how the concept of the rule Yukhtaru Ahwanu Syarraini is applied and to what extent it aligns with judges’ legal considerations in the decision to minimize harm. This study uses a normative legal research method with conceptual, statutory, and case approaches. The data sources consist of primary legal materials in the form of court decisions and secondary legal materials, such as books of fiqh rules, legislation, the Compilation of Islamic Law, and related scientific literature. Data analysis was conducted qualitatively through textual and descriptive qualitative analysis. The research findings indicate that the principle of